Metamorphization of Groundwater Chemistry Due to Soil Salinization (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article highlights the scientific basis of metamorphization of the chemical composition of natural waters on the basis of classical methods, as a result of which it is supposed to improve the ecological and geochemical state and as a consequence increase the fertility of saline soils.